Upper body subcutaneous adipose as a potential predictor for type 2 diabetes mellitus - Scepanovic, Andjelka; Vujovic, Slavica; Medin, Darko (Progress in Nutrition, 2019)
Background/Aim: Upper body skinfold measurements show association with type 2 diabetes mellitus (DM2). Precise predictive potential of the various points of the subcutaneous adipose tissue thickness in the upper body is not completely defined. The aim of this study was to examine the predictive potential of 4 subcutaneous fatty tissue spots (i.e., biceps, triceps, abdominal and subcapsular) regarding DM2 subjects diagnosed with disease before 60 years of age. Methods: Subcutaneous fatty tissue points were measured by a caliper in 108 subjects with DM2 who were diagnosed with the disease before the 60 years of age and compared with the same points of subcutaneous adipose tissue thickness of 112 control group subjects. Results: Skinfold measurments parameters were higher in DM2 subjects compared to controls (p